The three-axes model of planning in physical education (El modelo de planificación de tres ejes en Educación Física) - Jesús Viciana; Daniel Mayorga-Vega (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The high complexity of planning Physical Education is due to the great quantity of factors that influence its process. Consequently, many doubts appear in the decision-making process of any formational stage of Physical Education teachers. There is a lack of theoretical-practical tools that help teachers to be their own constructors of their curriculum by helping them to design their own proposals, instead of using proposals made by others. The main purpose of this study was to provide Physical Education teachers a theoretical and practical framework, which will guide them in the decisional making process during planning, in order to include in their teaching all the influential factors that need to be taken into account. The three-axes model of planning is discussed as a guide for planning Physical Education, helping teachers through practical recommendations and proposing strategies in each axis in order to prepare an effective Physical Education planning.